Improved Indonesian Language Learning Achievement Through Powerpoint Media for Class I Students of SD N 1 Ngemplak - Mujinem Mujinem (Universitas Sebelas Maret, 2022)
The purpose of this research was to improve the Indonesian language learning achievement of class I students elementary school with PowerPoint media in slide form. The research conducted was a Classroom Action Research (PTK) with two cycles. The stages of each cycle are planning, implementation, observe and reflect. Each meeting carries out a pre-test and post-test to determine student progress. In the pre-cycle, the average class score below the specified KKM was 75 and only 10 out of 18 students completed the KKM or only 55.5% of students completed the KKM. In the first cycle learning improvement with a percentage of 77.8% and using PowerPoint media in the learning improvement process. At this stage there are still 22.2% of students who have not met the KKM, so they continue with the second cycle of learning improvements. In the end, in learning cycle 2 there was an increase in the effectiveness of using PowerPoint media with a percentage increase of 88.9%. These results show that using PowerPoint media in the form of slides can improve students'learning achievements, sepecially class I Indonesia ata SDN 1 Ngemplak.